Windjammer : the voyage of the Christian Radich - Shute, James L.; Weegee, 1899-1968; Gould, Morton, 1913-1996; Strohmaier, David (Flicker Alley collection., 2012)
"Come on board the magnificent Norwegian square-rigger as it sails its spectacular 17,000 mile journey, manned by a crew of young sailors-in-training, all photographed in the widescreen splendor of Cinemiracle, Cinerama's only true competitor to thrill 1950's audiences by sheer size and clarity. Now digitally remastered in the unique "Smilebox" curved screen simulation, the color, the music, and the true artistry of this classic are reborn. Embarking from Oslo, Norway, the ship sets out across the Atlantic with a storm-tossed stop in Madeira, where New Year's festivities entice the young crewmen to enjoy Portuguese musical celebrations and heart racing rides in basket sleds down steep cobblestone streets. After that, it is on to Willemstad, Curacao, where the young sailors take part in Dutch festivities. They catch a courtyard performance of Pablo Casals in San Juan, Puerto Rico, and in Port-of-Spain, Trinidad, they re greeted by native steel bands and Calypso singers. By the time they arrive in New York, the Cinemiracle cameras offer a kaleidoscopic treat of color and sound created by famed photographer Arthur Weegee Fellig. A later encounter with the U.S. Navy Task Force makes for a grand promenade of ships, and when underwater shots of frogmen and a submarine emerge from the depths to reveal the Windjammer on the open sea, Cinemiracle becomes the true star of this breathtaking story. Morton Gould's top-notch score, along with a fine variety of music throughout the picture, sounds perfect in Cinemiracle's 7-channel sound recording" -- Container.